(untitled) (GIST – Education and Learning Research Journal, 2013)
This study explores tensions between three Iranian EFL teachers’ beliefs and practices with respect to teaching culture. The teachers were observed and interviewed over a period of eight weeks. The observations provided insight into how they taught culture in practice, while the interviews tried to elicit their beliefs. Drawing on the distinction between what they perceived as ideal and what they did in practice illustrated some differences between the two. It is argued that these tensions between beliefs and practices lead teachers with different beliefs to act similarly in practice. Claims are also made about the probable roots of the tensions which have been grouped into two main categories of macro-scale decisions by educational system and micro-scale preferences of learners and teachers. Finally, a number of implications for curriculum developers and teacher education programs are also made.